Silicone versus Metallic Tracheobronchial Stents for Malignant Central Airway Obstruction: A Systematic Review and Meta-Analysis (JBN (Jurnal Bedah Nasional), 2026)
Introduction: Malignant central airway obstruction (MCAO) is a critical complication of advanced thoracic malignancy that can rapidly lead to respiratory failure. Airway stenting remains one of the most effective palliative interventions, yet the relative efficacy and safety of silicone versus metallic stents remain uncertain.Objective: This meta-analysis aimed to compare clinical outcomes between silicone and metallic tracheobronchial stents in patients with malignant central airway obstruction. Methods: A systematic search was conducted across PubMed, Cochrane Library, and ScienceDirect databases from inception to October 2025. Studies were included if they compared silicone and metallic stents in adult patients with MCAO and reported at least one relevant outcome. Data extraction and quality assessment followed PRISMA guidelines, and pooled analyses were performed using random- or fixed-effects models as appropriate. The primary outcomes were overall complication rate, short-term (30-day) mortality, dyspnea symptom improvement, and incidence of granulation tissue formation.Results: Seven comparative cohort studies encompassing 358 patients were included. The pooled analyses revealed no statistically significant difference between silicone and metallic stents for overall complications (RR = 1.13, 95% CI 0.61–2.09, p = 0.71), 30-day mortality (RR = 0.97, 95% CI 0.80–1.17, p = 0.72), dyspnea improvement (RR = 1.03, 95% CI 0.74–1.43, p = 0.87), or granulation tissue formation (RR = 1.09, 95% CI 0.61–1.96, p = 0.78). Moderate heterogeneity was observed for complication and granulation outcomes but did not affect the direction of results. Both stent types achieved similar technical success, airway patency, and symptomatic relief.Discussion: The results indicate that silicone and metallic stents provide comparable clinical benefits and safety profiles for palliative management of malignant airway obstruction. The minor differences observed across studies likely reflect variations in device design, airway anatomy, and procedural expertise rather than material superiority. Given the absence of clear advantage for either stent, clinical decision-making should focus on individualized patient factors and procedural logistics.Conclusion: Silicone and metallic tracheobronchial stents demonstrate equivalent performance in the palliation of malignant central airway obstruction. The choice between them should be guided by patient condition, airway anatomy, and operator experience rather than intrinsic material properties. Future prospective studies incorporating hybrid and customized stent technologies are needed to define optimal strategies for airway restoration in advanced thoracic malignancy.
Keywords: Malignant central airway obstruction; tracheobronchial stent; silicone stent